Successful Control of Hepatitis B Virus Reactivation following Restart of Ibrutinib in Chronic Lymphocytic Leukaemia - Tjønnfjord, Sara Kristina Viberg; Tjønnfjord, Eirik Brekka; Konopski, Zbigniew; Tjønnfjord, Geir Erland (Case Reports in Hematology, 2021)
Ibrutinib is a targeted therapy drug that blocks the activity of Bruton’s tyrosine kinase, and it is an approved treatment for several mature B-cell malignancies including chronic lymphocytic leukaemia (CLL). Side effects include infections, cytopenia, nausea, and diarrhoea. In this report, we describe a case of hepatitis B reactivation in a female CLL patient undergoing treatment with ibrutinib. Diagnosis was confirmed with highly elevated hepatitis B virus DNA and a prior blood sample confirmed previous exposure. Ibrutinib was paused, and antiviral therapy was initiated with prompt clinical improvement. Ibrutinib was reinitiated shortly after clinical improvement. Thus, our case report demonstrates that systematic HBV screening is essential before starting treatment with ibrutinib. We suggest that antiviral prophylaxis is considered for patients at risk of reactivation, and ibrutinib may be continued following HBV reactivation with proper antiviral treatment.